Hypertonic Saline in Conjunction with High-Dose Furosemide Improves Dose–Response Curves in Worsening Refractory Congestive Heart Failure. Issue 10 (October 2015) - Paterna, Salvatore; Gaudio, Francesca; Rocca, Vincenzo; Balistreri, Fabio; Greco, Massimiliano; Torres, Daniele; Lupo, Umberto; Rizzo, Giuseppina; Pasquale, Pietro; Indelicato, Sergio; Cuttitta, Francesco; Butler, Javed; et al.
Abstract Introduction Diuretic responsiveness in patients with chronic heart failure (CHF) is better assessed by urine production per unit diuretic dose than by the absolute urine output or diuretic dose. Diuretic resistance arises over time when the plateau rate of sodium and water excretion is reached prior to optimal fluid elimination and may be overcome when hypertonic saline solution (HSS) is added to high doses of furosemide. Methods Forty-two consecutively hospitalized patients with refractory CHF were randomized in a 1:1:1 ratio to furosemide doses (125 mg, 250 mg, 500 mg) so that all patients received intravenous furosemide diluted in 150 ml of normal saline (0.9%) in the first step (0–24 h) and the same furosemide dose diluted in 150 ml of HSS (1.4%) in the next step (24–48 h) as to obtain 3 groups as follows: Fourteen patients receiving 125 mg (group 1), fourteen patients receiving 250 mg (group 2), and fourteen patients receiving 500 mg (group 3) of furosemide. Urine samples of all patients were collected at 30, 60, and 90 min, and 3, 4, 5, 6, 8, and 24 h after infusion. Diuresis, sodium excretion, osmolality, and furosemide concentration were evaluated for each urine sample. Results After randomization, 40 patients completed the study. Two patients, one in group 2 and one in group 3 dropped out. Patients in group 1 (125 mg furosemide) had a mean age of 77 ± 17 years, 43% were male, 6 (43%) had heart failure with a preserved ejection fraction (HFpEF), and 64% were in New York Heart Association (NYHA) class IV; the mean age of patients in group 2 (250 mg furosemide) was 80 ± 8.1 years, 15% were male, 5 (38%) had HFpEF, and 84% were in NYHA class IV; and the mean age of patients in group 3 (500 mg furosemide) was 73 ± 12 years, 54% were male, 6 (46%) had HFpEF, and 69% were in NYHA class IV. HSS added to furosemide increased total urine output, sodium excretion, urinary osmolality, and furosemide urine delivery in all patients and at all time points. The percentage increase was 18, 14, and 14% for urine output; 29, 24, and 16% for total sodium excretion; 45, 34, and 20% for urinary osmolarity; and 27, 36, and 32% for total furosemide excretion in groups 1, 2, and 3, respectively. These findings were translated in an improvement in the furosemide dose–response curves in these patients. Conclusion These results may serve as new pathophysiological basis for HSS use in the treatment of refractory CHF.